The history of displacement and forced settlement in West Kalimantan, Indonesia: implications for co-managing Danau Sentarum wildlife reserve - Wadley, R.L. (Berghahn Books, 2002)
The history of local settlement in conservation areas, even that occurring prior to conservation activities, is of great value in efforts to co-manage protected resources. It shows how local people came to be where they are now, and how they view the local landscape. It also indicates how reserve resources have been shaped by the people who have relied on them in the past; and it provides insight into present and future conditions, such as how resource competition between reserve residents is and might be structured and perceived. Thus, in conjunction with studies aimed at understanding present local resource use, attention needs to be given to settlement history in conservation areas as one critical component of the local condition. This paper focuses on the history of population change in and around Danau Sentarum Wildlife Reserve in West Kalimantan, Indonesia, and its implications for co-management. There are numerous communities from two different ethnic groups - Iban swidden farmers and Melayu fishers - located within and around the reserve core, relying to various degrees on its resources. The demographic history of the lakes area is marked by population displacement and forced settlement. Over the years the Iban and the Melayu settled, used, and abandoned the area as wars and raiding ebbed and flowed. Today with a growing local population and increased resource competition, the reserve faces many critical challenges to its future.